Marine Turtles, Ecosystem Services and Human Welfare in the Marine Ecosystems of the Caribbean Sea: A Discussion of Key Methodologies - Sonja S. Teelucksingh; Scott Eckert; Paulo A.L.D. Nunes (Études Caribéennes)
It is increasingly recognized that maintaining biodiversity is of fundamental importance toward sustaining human livelihoods. One of the major assets of the region identified as “Latin America and the Caribbean” (LAC) is its biological wealth; by extension, the continued biodiversity loss of the LAC region is seen as one of the world’s principal environmental problems. The marine resources of Caribbean Sea are of vital economic, ecological and social importance to the LAC region, and are under particular threat. Marine turtles play vital roles throughout the Caribbean Sea both in terms of ecological functions and human welfare. Conservation efforts in this direction can often depend on the ability to place a value on welfare changes associated with the loss of ecosystem goods and services into which biodiversity plays an integral role.Using the ecosystem service categories of the Millennium Ecosystem Assessment, this paper discusses from an inter-disciplinary perspective the methodologies associated with linking marine turtles, ecosystem services and human welfare. While the main economic benefit to be currently valued may stem from the eco-tourism potential surrounding turtle nesting sites, for a true picture of the environmental resources upon which this service depends, it is necessary to also identify the other provisioning, regulating and cultural services of the resource. In this way, human welfare impacts can be more truly judged, and effective resource management can be undertaken.